Christus in der russischen Literatur Ein Gang durch die Literaturgeschichte von ihren Anfaengen bis zum Ende des 20. Jahrhunderts - Kasack, Wolfgang (Arbeiten und Texte zur Slavistik, 1999)
This book describes representations of Christ in Russian literature from the beginning to the end of the twentieth century. The analysis of the works of more than a hundred writers illustrates the great religious and formal diversity of the implementation of this motif, thereby expanding the overall conception of each individual author and of the development of Russian literature. It also shows its embedding and independence within European intellectual history and its dependence on the political development of the Soviet Union. The anthology attached to this issue contains 100 partly complete and partly excerpted text examples in Russian. Scientific literature with anthology in Russian.